COMBINATION WARM WATER FOOT SOAK THERAPY WITH RED GINGER AND BENSON THERAPY IN HYPERTENSIVE ELDERLY WITH ANXIETY NURSING PROBLEM: CASE REPORT - Putri Juniar Pangesti; Wahyudi Mulyaningrat; Annas Sumeru (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Introduction: Hypertension is a disease that most often occurs in the elderly. The problem of hypertension in the elderly causes psychological problems, one of which is anxiety. The anxiety experienced by the elderly can worsen their health condition and can also reduce their quality of life. For this reason, intervention is needed to reduce anxiety, namely by providing a combination of warm water foot soak therapy with red ginger and benson therapy. Objective: This case study aims to determine the effect of giving a combination of warm water foot soak therapy with red ginger and benson therapy on anxiety in hypertensive elderly . Method: This research is a case study by implementing interventions according to EBN. The intervention carried out was a combination of warm water foot soak therapy with red ginger and benson therapy which was carried out for 10 minutes for 7 days. The research subject was 1 person. The subject is hypertensive elderly with anxiety nursing problems. Results: After intervention for 7 days, the post-test results for anxiety levels using the HARS (Hamilton Rating Scale for Anxiety) instrument showed a score of 8 (no anxiety). This score decreased when compared with the results of the pre-test anxiety level which received a score of 19 (mild anxiety), which means the client's anxiety decreased from mild anxiety to no anxiety. Conclusion: Providing a combination intervention of warm water foot soak therapy with red ginger and benson therapy for 7 days can reduce anxiety levels in hypertensive elderly.